TRIM44 enhances autophagy via SQSTM1 oligomerization in response to oxidative stress - Yuqin Wang; Lin Lyu; Trung Vu; Nami McCarty (Scientific Reports, 2024)
Abstract The deubiquitinase tripartite motif containing 44 (TRIM44) plays a critical role in linking the proteotoxic stress response with autophagic degradation, which is significant in the context of cancer and neurological diseases. Although TRIM44 is recognized as a prognostic marker in various cancers, the complex molecular mechanisms through which it facilitates autophagic degradation, particularly under oxidative stress conditions, have not been fully explored. In this study, we demonstrate that TRIM44 significantly enhances autophagy in response to oxidative stress, reducing cytotoxicity in cancer cells treated with arsenic trioxide. Our research emphasizes the critical role of the posttranslational modification of sequestosome-1 (SQSTM1) and its importance in improving sequestration during autophagic degradation under oxidative stress. We found that TRIM44 notably promotes SQSTM1 oligomerization in both PB1 domain-dependent and oxidation-dependent manners. Furthermore, TRIM44 amplifies the interaction between protein kinase A and oligomerized SQSTM1, leading to enhanced phosphorylation of SQSTM1 at S349. This phosphorylation event activates NFE2L2, a key transcription factor in the oxidative stress response, highlighting the importance of TRIM44 in modulating SQSTM1-mediated autophagy. Our findings support that TRIM44 plays pivotal roles in regulating autophagic sensitivity to oxidative stress, with implications for cancer, aging, aging-associated diseases, and neurodegenerative disorders.